The spatial-temporal structure of the magnetic field of Ukraine's territory: assessment of the contribution of internal and external sources - M.I. Orlyuk; A. V. Romenets; P. V. Sumaruk; Yu. P. Sumaruk; T. P. Sumaruk (Геофизический журнал, 2012)
Estimation of c ontribution of those or other sources in total magnetic field of the Earth is important i n c onnection wi th s eparation of i ts c onstituents with the p urpose of research of their nature, m echanism of origin etc. In this article s ome aspects of s ubdivision of internal and external s ources of the magnetic field of the E arth are c onsidered, as well as estimation of c ontribution of different s ources in the total fi eld and its variations is given. F or the s olving of the p rob-lem results of observations have been used of Ukrainian magnetic observatories fi rst of all.